Learning Media based on Augmented Reality Game - Sudarmilah, Endah; Ustia, Nurul; Nuryanto Bakhtiar, Dony (International Journal of Engineering and Technology, 2019)
Augmented reality serious game has benefits in the fields of psychology, health, and education. The learning process using AR media has a potential to be developed. The study aimed to utilize Augmented Reality Educational Game (AR EduGame) as a learning media for elementary school students that is entertaining in the form of video games but can stimulate students' cognitive. The software prototype was designed, tested by the black-box method, and assessed by expert judgment method (elementary school teachers as experts) and usability assessment (students as users). The implementation results show that the AR EduGame was had quality and feasible learning media with the percentage of interpretation of more than 80% by both users and experts. It could be concluded that these AR EduGames can be considered a quality learning media especially in learning Indonesian Culture regarding gamelan and traditional dances.Â Â